A review of the scientific literature concerning the effectiveness of mineral trioxide aggregate in conservative dentistry (International Journal of Food and Nutritional Sciences, 2022)
This literature study sought to evaluate the clinical performance of MTA in order to determine the amount of evidence for its efficacy in essential pulp therapy, perforation repair, and retrograde root canal filling. An exhaustive literature search was conducted using the Internet databases PubMed/MEDLINE. This study analysed a total of 58 papers, of which 2 were systematic reviews/meta-analyses, 9 were randomised controlled trials (RCTs), and the remainder fell into other categories. As a direct capping material, mineral trioxide aggregate (MTA) provided superior pulp protection than calcium hydroxide. As a perforation repair material, MTA displayed outstanding in vitro sealing properties. In clinical trials, MTA resulted in normal healing of periodontal tissues surrounding a hole. Therefore, it may be stated that MTA has a strong potential for perforation correction. MTA is the most promising material for retrograde root canal fillings, exhibiting normal healing in both short- and long-term clinical outcomes.